Intra-articular treatment of knee osteoarthritis: from anti-inflammatories to products of regenerative medicine. Issue 2 (2nd April 2016) - Richards, Masters M.; Maxwell, Joshua Shane; Weng, Lihui; Angelos, Mathew G.; Golzarian, Jafar
ABSTRACT: Objectives : Knee osteoarthritis (OA) is a debilitating condition that may ultimately require total knee arthroplasty (TKA). Non-operative treatments are bracing, oral analgesics, physical therapy, and intra-articular knee injection (IAKI). The objective of this paper is to provide a systematic literature review regarding intra-articular treatment of knee OA and insight into promising new products of regenerative medicine that may eventually have a substantial effect on treatment. Methods : A literature search was executed using Medline, Cochrane, and Embase with keywords "knee osteoarthritis" and "injection." Specifically, 45 articles that discussed intra-articular knee injection using corticosteroids, hyaluronic acid, analgesics, local anesthetics, and newer products of regenerative medicine, such as platelet-rich plasma (PRP) and mesenchymal stem cells (MSC), were analyzed. Of these, eleven were level 1, three were level 2, twelve were level 3, two were level 4, and seventeen were level 5 evidence. Papers included animal models. Results : Local anesthetics have potential side effects and may only be effective for a few hours. Morphine and ketorolac may provide significant pain relief for 24 hours. Corticosteroids may give patients weeks to months of effective analgesia, but complications may occur, such as systemic hyperglycemia, septic arthritis, and joint degradation . Hyaluronic acid is a natural component of synovial fluid, but efficacy with respect to analgesia is controversial. Platelet-rich plasma formulations, autologous conditioned serum, autologous protein solution, and mesenchymal stem cell injections contain anti-inflammatory molecules and have been proposed to attenuate joint destruction or potentially remodel the joint. Conclusions : Currently, knee OA treatment does not address the progressively inflammatory environment of the joint. More investigation is needed regarding products of regenerative medicine, but they may ultimately have profound implications in the way knee OA is managed.